THE EFFECT OF USING ANAGRAM GAME IN IMPROVING STUDENTS’ VOCABULARY MASTERY AT THE ELEVENTH GRADE OF SMA NEGERI 4 BAUBAU - Wa Ode Lulu Asranida; Nur Melansari (English Education Department, 2019)
This study is aimed to find out the effect of using anagram game to improve students’ vocabulary mastery at the eleventh grade of SMA Negeri 4 Baubau. The research used quantitative approach and applied quasi experimental design. The population of this research was the eleventh grade students of SMA Negeri 4 Baubau. The number of population was 185 students. The sample was class XI MIA 5 as the experimental class and class XI MIA 1 as the control class in which the total of both classes was 60 students. The sampling technique in this research was cluster random sampling. The instrument of the research was tests in the form of multiple choices. The data obtained were analized by using SPSS 22.0 program. The result of the research shows that the mean score of experimental class in pre-test is 55.17 and the mean score in pre-test of control class is 47.50, while the mean score of experimental class in post-test is 72.83 and the mean score of control class in post-test is 56.83. The data shows that the mean score of experimental class is higher than the control class. The result of hypotesis testing is found that tcount 57.44 > ttable 2.021 and the probability value (sig.(2-tailed)) 0.000 < 0.05 which means that Ha is accepted and H0 is rejected. Thus, there is a significant effect of using anagram game in improving students’ vocabulary mastery at eleventh grade of SMA Negeri 4 Baubau.